The significance of the distribution of the indicators of humoral and cell immunity and their role in the pathogenesis of bronchial asthma in children with the position of system analysis - Chernuskyi, Viacheslav; Popov, Mykola; Letiaho, Hanna; Hovalenkova, Olha; Tolmachova, Svitlana; Popova, Alisa (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2021)
Bronchial asthma is one of the common diseases in children of different ages. In recent years, around the world, including in Ukraine, there is a trend towards its sustainable growth. To date, there are no methods of systemic immunodiagnostics that would allow with high diagnostic accuracy to identify clinical forms and severity of asthma, which would allow more fully reveal the pathogenetic mechanisms and individualize approaches to the treatment of asthma in children. The aim of this work was to study the hierarchy of immunological parameters in the pathogenetic matrix, which will determine the features of clinical forms and severity of asthma in children on the basis of systematic analysis. A comprehensive clinical and immunological examination of 176 children with asthma aged 6 to 15 years. To detect the autoimmune component used lipopolysaccharide antigens obtained from homologous cell-tissue structures of the trachea, bronchi and lung tissue from sectional samples of the bronchopulmonary system from accidentally killed children with group I (0) blood 2–4 hours after death. The level of autoantibodies to lipopolysaccharide antigens of the bronchopulmonary system was determined by quantifying the autoantibody index – Qφ. As a result of the study for the first time to improve the diagnosis and differentiation of clinical forms and severity of asthma from the standpoint of system analysis was developed immunodiagnostic complex, which took into account the degree of deviation from the norm values (Student’s t-test, t = 1.96) and their distribution in pathogenetic matrix. This approach to ranking the positions of immunological parameters allowed to determine the features of humoral and cellular immunity, the process of apoptosis of cell-tissue structures of the bronchopulmonary system and the autoimmune component in the pathogenesis of asthma in children, which opens approaches to individualization of pathogenetic therapy.